Environmental Management of Agricultural Enterprises in the Context of European Environmentally - Friendly Food System - KUPALOVA, Halyna; GONCHARENKO, Nataliia; ANDRUSIV, Uliana (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
Strengthening international environmental regulation, implementation of a European strategy for a sustainable food system form new environmental requirements for producers and exporters of agricultural products. To meet new environmental requirements, avoiding environmental barriers to exports, agricultural enterprises must improve environmental management. The article improves environmental management in terms of the formation of the environmental strategy of agricultural enterprises in the context of the European environmentally-friendly food system. It was found that improving the efficiency of activities, the requirements of suppliers or customers and improving the company's image among stakeholders are the main incentives for the implementation of international environmental management standards in agricultural enterprises. It has been determined that in modern conditions the tasks of environmental management are expanding in terms of ensuring the competitiveness of agricultural enterprises by reducing the chemicalization of production processes and the carbon footprint. The stages of strategic planning in the environmental management system of export-oriented agricultural enterprises have been substantiated. An economic and mathematical model of production optimization, taking into account environmental factors, has been proposed for strategic planning in the environmental management system of agricultural enterprises.